Penyuluhan Pemenuhan Gizi dalam Pencegahan Stunting pada Balita di Desa Rawang Itek Kec. Panton Labu Kab. Aceh Utara - Dian Vita Sari; Fatmawati Fatmawati; M. Nasir Nasir; Saifuddin Muhammad Jalil; Dedy Ahmady (Jurnal Pengabdian kepada Masyarakat Wahana Usada, 2023)
Background One of the health problems that still exist in Indonesia is the death of children under five years of age (toddlers). malnutrition status is still be the big cause. The condition of providing nutrition to children in Indonesia is very bad compared to the nutrition of children in the world. Therefore, this is a very important to children get good and balanced nutritional intake to support the child's growth in the future and permanently and at high risk, namely stunting. The purpose of this community service is to provide counseling on nutrition fulfillment in preventing stunting in toddlers. The method of implementing community service is directly using counseling methods, and physical examination of toddlers at posyandu in Rawang Itek Village, Panton Labu District, North Aceh Regency. The results of counseling and physical examinations at the posyandu indicated that the nutrition of toddlers in Rawang Itek village was in a good category, only mothers who had toddlers were still not doing frequent and routine health checks up for toddlers by bringing their children to the posyandu. Conclusion of community service it can be concluded that the role of the mother is very important in the development of toddlers. Toddlers must be routinely brought to the posyandu and carry out physical examinations and checks for nutritional status.